A Faculdade de Filosofia de Natal: projeto educacional da Associação de Professores do Rio Grande do Norte (1950-1963) - Alves, Amanda Vitória Barbosa (2024)
This study aims to analyze the representations and educational practices implemented at the Faculty of Philosophy of Natal within the educational project promoted by the Associação de Professores do Rio Grande do Norte (APRN), from 1950 to 1963. This period encompasses the initial ideas for establishing the Faculty through to the moment when APRN ceased to support the institution. APRN was established in the 1920s by a group of primary school teachers trained at the Escola Normal de Natal. This group’s educational project aimed to combat illiteracy in the state and defend teachers' interests. To this end, they proposed mechanisms for disseminating pedagogical ideas, such as the Pedagogium magazine, as well as the construction of educational institutions and teacher training centers to bring these pedagogical ideas to life and spread their educational project. Thus, in 1955, APRN established the Faculty of Philosophy of Natal, an institution that would train teachers at the higher education level to work in secondary and normal education in Rio Grande do Norte. Its purpose was to prepare intellectual workers for technical roles, as well as to conduct research in various cultural fields that constitute the object of teaching. For this research, the use of printed sources was of fundamental importance, especially periodical documents such as the newspapers and magazines circulating at the time, including the newspaper A República (1956–1960) and Pedagogium magazine (1948–1953). We analyzed these sources based on the theoretical and methodological assumptions of Cultural History, in order to historically indicate how a specific social reality was constructed, practiced, conceptualized, and appropriated in different places and how individuals’ everyday practices contribute to the construction of a historical identity (Chartier, 1990; 2002); (Certeau, 1994); (Rüsen, 2001); (Burke, 1991); (Le Goff, 2005). The Faculty of Philosophy of Natal was created in a historical and social context of higher education expansion in the state. It was directed by Edgar Barbosa, a professor, magistrate, and humanist intellectual chosen by APRN, who sought to impart his philosophical and pedagogical influence on the institution he directed. Throughout its history, the Faculty of Philosophy offered complementary courses, training graduates and licensed professionals to work in education in Rio Grande do Norte. Finally, we found that the APRN’s educational project, at the Faculty of Philosophy, was to train teachers grounded in a humanistic philosophical and pedagogical perspective, valuing artistic, literary, philosophical, and scientific knowledge and integrating these aspects with teaching activities.